Customer Priorities in Sustainable Food Sourcing within Jakarta’s Hospitality Sector - Tutur Wicaksono; Ongky Alex Sander (Journal of Tourism and Economic, 2025)
This study investigates consumer preferences regarding sustainable food sourcing practices in Jakarta's hospitality sector, a region undergoing significant urban transformation with an increasing focus on sustainability. Despite global trends towards sustainable sourcing, Jakarta’s hospitality sector faces challenges in adopting such practices due to local economic and logistical constraints. Utilizing the Kano Model, this research explores key sustainable food sourcing practices, such as local sourcing, certified suppliers, waste redistribution, and eco-labeling, through a survey conducted with 187 participants. The study categorizes consumer preferences into "must-be," "one-dimensional," "attractive," and "indifferent" categories, identifying waste redistribution, green logistics, and eco-labeling as the highest priority practices. These findings provide actionable insights for hospitality businesses, enabling them to better align sustainability initiatives with consumer expectations, fostering environmental responsibility while meeting customer demands in Jakarta's evolving hospitality landscape. The results offer a nuanced understanding of local consumer preferences, contributing to the broader field of sustainable hospitality practices in emerging economies.